Healthy lifestyle in children and adolescents and its association with subjective health complaints: findings from 37 countries and regions from the HBSC Study - Marques, Adilson (2019)
Background: It is important to clearly understand the factors associated with subjective health complaints. The study aimed to investigate the relationship between subjective health complaints, several health behaviors, and a composite measure of healthy lifestyle. Methods: Data were from the Health Behaviour in School-aged Children (HBSC) 2014 international database. Participants were 167,021 children and adolescents, aged 10–16 years, from 37 countries and regions. A composite score of healthy lifestyle was created using a combination of daily physical activity, daily consumption of fruit and vegetables, <2 hours spent daily in screen-based behaviors, no drinking, and no smoking. The subjective health complaints assessed were headaches, stomach aches, backache, dizziness, feeling low, irritability, nervousness, and sleep difficulties. Results: Those who engage in physical activity every day, spend less than two hours a day in screen-based behaviors, do not drink alcohol, and do not smoke tobacco presented a higher likelihood of not having subjective health complaints. A healthy lifestyle was significantly related to having less of all the subjective health complaints. Those with a healthy lifestyle were 50% (OR = 0.5, 95% CI: 0.5–0.6, p < 0.001) less likely to have multiple health complaints. Conclusions: Healthy behaviors and healthy lifestyles are related with less subjective health complaints and less multiple health complaints.